The prevalence of food allergy in cesarean-born children aged 0–3 years: A systematic review and meta-analysis of cohort studies - Yang, Xiaoxian; Zhou, Chuhui; Guo, Chentao; Wang, Jie; Chen, Innie; Wen, Shi Wu; Krewski, Daniel; Yue, Liqun; Xie, Ri-hua (Frontiers in Pediatrics, 2023)
Purpose Previous studies reported a higher risk of food allergy for cesarean-born children than vaginal-born children. This study aims to systematically compare the prevalence of food allergy among cesarean-born and vaginal-born children aged 0–3 years. Methods Three English and two Chinese databases were searched using terms related to food allergies and cesarean sections. Cohort studies that reported the prevalence of food allergy in cesarean-born and vaginal-born children aged 0–3 years were included. Two reviewers performed study selection, quality assessment, and data extraction. The pooled prevalence of food allergy in cesarean-born and vaginal-born children was compared by meta-analysis. Results Nine eligible studies, with 9,650 cesarean-born children and 20,418 vaginal-born children aged 0–3 years, were included. Of them, 645 cesarean-born children and 991 vaginal-born children were identified as having food allergies. The pooled prevalence of food allergy was higher in cesarean-born children (7.8%) than in vaginal-born children (5.9%). Cesarean section was associated with an increased risk of food allergy [odds ratio (OR): 1.45; 95% confidence interval (CI): 1.03–2.05] and cow's milk allergy (OR: 3.31; 95% CI: 1.98–5.53). Additionally, cesarean-born children with a parental history of allergy had an increased risk of food allergy (OR: 2.60; 95% CI: 1.28–5.27). Conclusion This study suggests that cesarean sections was associated with an increased risk of food and cow's milk allergies in children aged 0–3 years. Cesarean-born children with a parental history of allergy demonstrated a higher risk for food allergy than did vaginal-born children. These results indicate that caregivers should be aware of the risks of food allergies in cesarean-born children, reducing the risk of potentially fatal allergic events. Further research is needed to identify the specific factors affecting food allergies in young children. Systematic Review Registration http://www.crd.york.ac.uk/prospero, identifier: International Prospective Register of Systematic Reviews (NO. CRD42019140748).